Exploring the Functionality of Microbes in Fermented Foods: Technological Advancements and Future Directions - Akanksha Singh; Sanjay Kumar (Fermentation)
Fermentation is a promising food processing technique that has been used throughout history for its role in food preservation, the enhancement of nutritional content, and improvement of sensory attributes. Beyond the primary probiotic benefits, microorganisms in fermented foods play a functional role in increasing nutrient bioavailability, exhibiting antimicrobial properties, producing bioactive compounds, and removing antinutritional factors. This review explores microbial diversity and its role in the production of fermented foods across different regions of the world through a dynamic market analysis. It also highlights recent biotechnological advancements in fermentation, specifically the use of omics, multi-omics, and precision fermentation. Omics technologies have been found to provide a deeper insight into microbial diversity, deciphering their metabolic pathways and functional interactions, whereas precision fermentation is being used for the manipulation of microbial processes to optimize the fermentation process and produce the desired attributes in fermented foods. Various sustainable substrates have also been used in the production of fermented foods, apart from the conventional ones. Interestingly, this review discusses the growing role of artificial intelligence, machine learning, and the Internet of Things in food fermentation, focusing on their potential to optimize processes, predict microbial interactions, and improve quality control, supported by relevant successful examples. The review also examines the current challenges faced by the fermented food industry, offering various mitigation strategies to overcome these obstacles. Possible future prospects are also explored. Through a combination of traditional methods and modern biotechnological innovations, functional fermentation is bound to transform the global food industry.